USING TASK-BASED INSTRUCTION IN DESIGNING ENGLISH LEARNING MATERIALS FOR NURSING STUDENTS AT STIK FAMIKA, INDONESIA - Wanci, Risman; Sujariati, Sujariati (Program Pascasarjana, UIN Alauddin Makassar, 2021)
The presentation of appropriate learning materials to students should be an essential concern for a lecturer because some students need the material in general, and there are also those who need it specifically. Accordingly, a lecturer needs to know the needs of the learning materials needed by students who will be taught before the material is given to them. The objectives of this research were to design a syllabus, lesson plan, and coursebook of English for nursing at Nursing College of Famika (STIK Famika), Makassar, Indonesia. A research method used was research and development. It applied five steps of ADDIE design (analyze, design, develop, implement, and evaluate). Qualitative descriptive was used to analyze the data collected. The results of this research recommended a syllabus, lesson plan, and coursebook (English learning materials for nursing students). The coursebook has seven units of learning materials, and the materials were designed based on task-based instruction. The lesson plan was designed after the syllabus design, the important things to be included in the syllabus and lesson plan are learning objectives, standard competence, basic competence, time allotment, indicators, learning materials, learning activities (lecturer and students’ activities), method, media, sources to be used, and evaluation. In designing the products (syllabus, lesson plan, and coursebook), the writer involved two lecturers (Nursing and English lecturers) to know their opinions regarding the design of the products. The research results are expected to be useful for the teaching and learning English at the nursing study program of STIK Famika, Makassar, Indonesia.